Blockchain and Smart Contract Application for Zakat Institution - Dhiaeddine Rejeb (International Journal of Zakat, 2020)
Blockchain is an open distributed database that carries out transactions on an open decentralized ledger. It is a technology that will probably be the source of a huge digital change especially in the financial sector. The application of this technology has started to take its first steps recently and its importance is undeniable in an emerging and expanding field such as Islamic finance. In this context, the purpose of this article is to study the integration of the blockchain and one of its important components, namely the smart contract in the management of the compulsory Islamic charity the zakat. To do this, we have developed a funding model linking all the stakeholders in question and the diversities of blockchain technology. We were thus able to conclude huge benefits and technical contributions in this context which encourages Islamic financial institutions to develop more models likely to support this technology without ignoring the compliance with the Islamic jurisprudence rules.